2022
DOI: 10.1002/epi4.12604
|View full text |Cite
|
Sign up to set email alerts
|

Clemizole and trazodone are effective antiseizure treatments in a zebrafish model of STXBP1 disorder

Abstract: CRISPR‐Cas9–generated zebrafish carrying a 12 base‐pair deletion in stxbpb1b, a paralog sharing 79% amino acid sequence identity with human, exhibit spontaneous electrographic seizures during larval stages of development. Zebrafish stxbp1b mutants provide an efficient preclinical platform to test antiseizure therapeutics. The present study was designed to test antiseizure medications approved for clinical use and two recently identified repurposed drugs with antiseizure activity. Larval homozygous stxbp1b zebr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(118 reference statements)
1
5
0
Order By: Relevance
“…In this experiment, the ZebVortrack system was used to evaluate a variety of antiseizure drugs, and the results showed that these antiseizure drugs could reduce the activity frequency of larval zebra sh and suppress the seizure-like behavior induced by PTZ, which is in accordance with previous reports [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 88%
“…In this experiment, the ZebVortrack system was used to evaluate a variety of antiseizure drugs, and the results showed that these antiseizure drugs could reduce the activity frequency of larval zebra sh and suppress the seizure-like behavior induced by PTZ, which is in accordance with previous reports [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 88%
“…Another treatment option that has been considered is to trial medications that interact with serotonin receptors. The screening of various antiseizure medications in a zebrafish model of STXBP1-related disorders identified Clemizole and Trazodone as medications that decreased ictal events [64]. These findings suggest that medications with serotoninreceptor-binding affinities could be an effective antiseizure medication option, although further research is needed.…”
Section: Treatmentmentioning
confidence: 96%
“…In recent years, a zebrafish animal model for STXBP1-related disorders has been developed [69,70]. Already these models have been used to screen antiseizure medications [64] and have been used to visualize in vivo network dynamics [59]. This may function to easily screen medications, as well as monitor changes in network dynamics.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recording chambers were placed on the stage of an upright microscope (Olympus BX-51W) and monitored continuously using a Zeiss Axiocam digital camera. Under visual guidance, gap-free LFP recordings (15 minute duration) were obtained from the optic tectum using a single-glass microelectrode (WPI glass #TW150 F-3) with approximately 1 µM tip diameter backfilled with 2 mM NaCl internal solution as described previously 29,[37][38][39][40] .…”
Section: Electrophysiology Assaymentioning
confidence: 99%